Juridic Review Concerning The Position Of Joint Assets After Post Divorce Analysis Of Civil Decision Number 343/Pdt.G/2020/Pa.Tte - Irnayanti Tjan; Rusdin Alauddin; Faissal Malik (IHSA Institute, 2022)
A marriage agreement is an agreement made before the marriage takes place and binds the two prospective brides who will be married, its contents regarding the issue of the distribution of assets between husband and wife which includes what belongs to the husband or wife and what is the responsibility of the husband and wife, or related to property. In the event of a divorce or death in one of the partners, usually a prenuptial agreement is made for legal purposes for each other's property, husband or wife. Making a prenuptial agreement is allowed as long as it does not conflict with law, religion and decency, moral values ??and customs. All legal actions related to joint property must have the consent of both parties, in this case husband and wife, if it is violated, the consequences of the act are one of the parties can file an objection. Based on the description above regarding the existence of joint property of husband and wife, there are many cases regarding this joint property, such as the case that was submitted to the Ternate Religious Court where between husband and wife who are going to divorce dispute their joint assets after the divorce decision has permanent legal force. Which aims to analyze how the mechanism for the distribution of joint property after divorce without a prenuptial agreement. and what are the legal consequences if one of the parties does not carry out the decision of the Religious Court judge regarding the distribution of joint property which already has permanent legal force. By using a normative juridical research method, which is a type of sociological legal research and can be referred to as field research, which examines the applicable legal provisions and what has occurred in people's lives. This study uses a statutory approach, a concept and case approach. Especially in this case regarding the analysis of the agreement in the Civil Code and the regulation of joint property and the strength of the judge's decision. From the results of the discussion, it was revealed that with respect to these objects, at trial the Defendant was also unable to show proof of ownership and year of acquisition, nor could the proposed witnesses explain the type, year of acquisition and status of the object, as well as during an on-site examination of the object. the intended object is not found, so that the object must be declared unproven and deserves to be declared unacceptable; Whereas based on the provisions of Article 37 of Law Number 1 of 1974 concerning Marriage jo. Article 97 Compilation of Islamic Law, because the marriage has been broken up due to divorce, then for the assets that are designated as joint property of the Plaintiff and Defendant, each Plaintiff and Defendant are entitled to one-half of the joint property. So that in the Court's Decision, the Judge granted the Plaintiff's claim in part and determined that the Plaintiff and Defendant were each entitled to (half) of the joint property